High-resolution proton nuclear magnetic resonance characterization of seminolipid from bovine spermatozoa. - JG Alvarez; BT Storey; ML Hemling; RL Grob (Journal of Lipid Research, 1990)
The high-resolution one- and two-dimensional proton nuclear magnetic resonance (1H-NMR) characterization of seminolipid from bovine spermatozoa is presented. The 1H-NMR data was confirmed by gas-liquid chromatography-mass spectrometric analysis of the partially methylated alditol acetates of the sugar unit, mild alkaline methanolysis of the glyceryl ester, mobility on normal phase and diphasic thin-layer chromatography (HPTLC), and fast atom bombardment mass spectrometry (FAB-MS). The structure of the molecule corresponds to 1-O-hexadecyl-2-O-hexadecanoyl-3-O-beta-D-(3'-sulfo)-galactopyranosyl- sn-glycerol.